2012
DOI: 10.17265/2159-5542/2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability, Cognitive Flexibility, Personal Need for Structure, and Rigidity

Abstract: IA (individual adaptability), COFL (cognitive flexibility), PNS (personal need for structure), and rigidity of attitudes, all have an aim in common to evaluate the person's self-perceived capacity to manifest a flexible or inflexible behavior in a given situation. However, these seemingly related concepts have rarely been investigated jointly. The goal of the present research is twofold: (1) to explore elements of discriminate and convergent validity of IA by relating it to COFL, PNS, and rigidity; and (2) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Other avenues for future research include the distinguishing of IAQ from similar constructs such as agility. Similarly to adaptability, the concept of agility does not have a single, accepted definition in the literature, with some descriptions including physical as well as cognitive elements (Hamtiaux & Houssemand, 2012; Pulakos et al, 2000; Sheppard & Young, 2006). If the narrower scope of learning agility is separated from the broader agility literature and its definition and measurement is explored, there is similar variation (De Meuse, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Other avenues for future research include the distinguishing of IAQ from similar constructs such as agility. Similarly to adaptability, the concept of agility does not have a single, accepted definition in the literature, with some descriptions including physical as well as cognitive elements (Hamtiaux & Houssemand, 2012; Pulakos et al, 2000; Sheppard & Young, 2006). If the narrower scope of learning agility is separated from the broader agility literature and its definition and measurement is explored, there is similar variation (De Meuse, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive flexibility includes “a person’s (a) awareness that in any given situation there are options and alternatives available, (b) willingness to be flexible and adapt to the situation, and (c) self-efficacy in being flexible” ( Martin and Rubin, 1995 , p. 623). Previous research has already shown a positive relationship between individuals’ adaptability and their cognitive flexibility ( Hamtiaux and Houssemand, 2012 ). In line with this, we propose that cognitive flexibility and adaptive leadership behavior are positively and strongly related as acting and leading in an adaptive way is not possible without flexibility in thinking.…”
Section: Studymentioning
confidence: 94%
“…Hence, adaptation of behavior to frequently changing situations is not a behavior that rigid leaders would be able to exhibit ( Steinmetz et al, 2011 ). Previous research has already shown that individual adaptability has a negative relationship with rigidity ( Hamtiaux and Houssemand, 2012 ). Therefore, we expect higher levels of adaptive leadership behavior to be associated with lower levels of rigidity.…”
Section: Studymentioning
confidence: 98%
“…To assess discriminant validity, we used the Personal Need for Structure (PNS) scale (Hamtiaux & Houssemand, 2012;Neuberg & Newsom, 1993). PNS (Neuberg and Newsom, 1993) was evaluated with the PNS scale incorporating two main components: "desire for structure" (4 items) and "response to lack of structure" (7 items).…”
Section: Personal Need For Structurementioning
confidence: 99%